IMPACT OF STREETSCAPING ON HUMAN PSYCHOLOGY - Trivedi, Kavya; Mishra, Soma Anil; Gehlot, Kunika (International Journal of Research -GRANTHAALAYAH, 2018)
This research is subjected to the study of the impact of street scape on human psychology. The study mainly focuses on the importance of the design of sidewalks on the street so that it can’t become the space for the criminal activities as described by the journalist jane Jacobs. The research also aims to study the role of urbanization in changing the street scaping of the cities. The study comprises of the statistical data which is the output of the survey conducted by the researcher and live case study of the streets of two cities i.e. Chandigarh and Pune.42% Part of the city are imbued with streets and therefore they play a vital role on the psychology of a human being. Keeping this in mind, the research is made on how streets could be designed in a manner that create the surrounding safe and happier to live.